2021
DOI: 10.1007/s00122-021-03897-w
|View full text |Cite
|
Sign up to set email alerts
|

GWAS and WGCNA uncover hub genes controlling salt tolerance in maize (Zea mays L.) seedlings

Abstract: Salt stress in uences maize growth and development. To decode the genetic basis and hub genes controlling salt tolerance is a meaningful exploration for cultivating salt-tolerant maize varieties. Herein, we used an association panel consisting of 305 lines to identify the genetic loci responsible for Na + -and K + -related traits in maize seedlings. Under the salt stress, seven signi cant single nucleotide polymorphisms were identi ed using a genome-wide association study, and 120 genes were obtained by scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 67 publications
0
49
0
Order By: Relevance
“…For example, ZmNC2 ( Na + CONTENT 2 ) and ZmNSA1 ( Na + CONTENT UNDER SALINE‐ALKALINE CONDITION ) were identified to confer the natural variation of shoot Na + in maize by using GWAS (Cao et al, 2020; Zhang et al, 2019). Our previous study also decoded the genetic architecture of Na + and K + content in maize seedlings and found seven SNPs controlling Na + /K + in shoot, root K + content, and K + transport coefficient (Ma et al, 2021). However, few studies have attempted to demonstrate the variations of Ca 2+ concentration in response to salt stress.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, ZmNC2 ( Na + CONTENT 2 ) and ZmNSA1 ( Na + CONTENT UNDER SALINE‐ALKALINE CONDITION ) were identified to confer the natural variation of shoot Na + in maize by using GWAS (Cao et al, 2020; Zhang et al, 2019). Our previous study also decoded the genetic architecture of Na + and K + content in maize seedlings and found seven SNPs controlling Na + /K + in shoot, root K + content, and K + transport coefficient (Ma et al, 2021). However, few studies have attempted to demonstrate the variations of Ca 2+ concentration in response to salt stress.…”
Section: Discussionmentioning
confidence: 90%
“…Our previous study also decoded the genetic architecture of Na + and K + content in maize seedlings and found seven SNPs controlling Na + /K + in shoot, root K + content, and K + transport coefficient (Ma et al, 2021).…”
Section: Candidate Gene Association Analysis Revealed the Potentially...mentioning
confidence: 89%
“…Transcriptome profiling has been widely used to analyze saltinduced gene expression in various plants (Zhu et al, 2019;Zhang et al, 2020;Ma et al, 2021). With the aid of RNA sequencing, significant pathways of differentially expressed genes (DEGs) are identified that would otherwise have been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Co-expression modules have been used to exhibit the interaction relationships between different function-associated genes [ 38 , 39 ]. In total, 8,577 DETs including 7,835 DE-PCTs and 742 DELs were used for constructing the co-expression modules via WGCNA (Table S9).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the shoot and root growth was more seriously inhibited under salt treatment in the salt-sensitive line BML1234 compared with the salt-tolerant line L2010-3 [ 28 ]. A total of 178 K single nucleotide polymorphisms (SNPs) existed between the two lines [ 39 ]. In the present study, considerable variations in transcript expression levels were found between BML1234 and L2010-3, which coincided with the large genetic variations between the two lines.…”
Section: Discussionmentioning
confidence: 99%